The Influence Of Tax Audit, Tax Avoidance And Company Risk On Company Involvement In Tax Amnesty Programs In Indonesia - Purwanti, Dyah; Kuncoro, Ari; Andriani, Arifah Fibri (Kesatuan Press, 2020)
This study aims to investigate the motivation of taxpayers for participating in the tax amnesty programs in Indonesia. At the end of 2016 to early 2017, the Government of Indonesia implemented a tax amnesty program. Through this research, we observed the profile of corporate taxpayers who voluntarily took part in the program. The results of this profile observation are useful for mapping the types of taxpayers’ motivation that are beneficial in increasing tax compliance. To achieve this goal, we observed the companies listed on the Indonesia Stock Exchange in the 2015-2017 period and then selected samples based on certain criteria. By using logistic regression, this study proves that the factors of tax audits, tax avoidance and business risk of the company encourage companies to join the tax amnesty program. These findings confirm that the company made use of the incentives offered by the tax amnesty program.